Pengujian Black Box pada Aplikasi Ecampus Menggunakan Metode Equivalence Partitioning - Pramudita, Rully (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics; Vol 4 No 2 (2020): INFORMATICS FOR EDUCATORS AND PROFESSIONAL : JOURNAL OF INFORMATICS (Juni 2020)DO - 10.51211/itbi.v4i2.1347, 2020)
Salah satu tahapan penting dalam pengembangan sebuah perangkat lunak yaitu tahap pengujian. Teknik testing dibagi menjadi dua yaitu black box testing dan white box testing. Pada penelitian akan menerapkan teknik pengujian black box . Teknik pengujian black box   terdiri dari, Equivalence Partitioning , Boundary Value Analysis / Limit Testing , Comparison Testing, Sample Testing, Robustness Testing, Behavior Testing, Requirement Testing, Performance Testing, Endurance Testing, Cause-Effect Relationship Testing . Salah satu yang akan diterapkan dalam penelitian ini yaitu teknik equivalence partitioning . Teknik ini ujicoba yang dilakukan berdasarkan tujuh tahapan, yaitu menentukan use case yang diuji, tentukan kriteria, definisikan partisi, buat data uji, buat kasus uji, lakukan pengujian dan evaluasi. Hasil pengujian nantinya akan menghasilkan feedback untuk masukan bagi pengelola ecampus.   Kata kunci: Aplikasi, Black box, Ecampus, Ekuivalence partitioning, Pengujian   Abstract:   One important stage in the development of a software is the testing phase. Testing techniques are divided into two namely black box testing and white box testing. In the study will apply black box testing techniques. Black box testing techniques consist of, Equivalence Partitioning, Boundary Value Analysis / Limit Testing, Comparison Testing, Sample Testing, Robustness Testing, Behavior Testing, Requirement Testing, Performance Testing, Endurance Testing, Cause-Effect Relationship Testing. One that will be applied in this research is equivalence partitioning technique. This technique is based on seven stages of testing, namely determining the tested use case, determining criteria, defining partitions, creating test data, making test cases, testing and evaluating. The test results will later produce feedback for input for ecampus managers.   Keywords : Application, Black box, Ecampus, Ekuivalence partitioning, Testing